Risk management in mudharabah financing in Islamic banks in Indonesia: a literature study analysis - Anggraeni, Novita Putri (Maliki Interdisciplinary Journal, 2024)
The presence of a banking system in a modern economy is a necessity that is difficult to avoid. As entities in the financial sector, both banking and industry are inseparably linked. They serve as a link between economic entities that have excess funds and those that need additional funds. This research uses the literature study method by collecting and processing the results of previous related or relevant research. The implementation of mudharabah financing requires careful consideration of staff expertise, time and costs in a continuous monitoring system, as well as building strong support and commitment from bankers and managers in the existing Islamic banking environment. Based on the results of the literature review on the analysis of mudharabah financing risk management in Islamic banking in Indonesia, it can be concluded that all articles used as references and made by previous studies are in line with the studies studied by researchers. The various kinds of risks faced by the Islamic banking sector in Indonesia are very diverse, including non-performing credit risk, liquidity risk, operational risk, expense risk, legal risk, benchmark risk, and fiduciary risk, funding risk, loss risk, fluctuations in business income, and inaccurate information from customers.